Symposium on Harold Netland's Religious Experience and the Knowledge of God - Seeman, Bradley N. 196X- (Philosophia Christi, 2023)
At the 2022 national meeting of the American Academy of Religion, the Evangelical Philosophical Society sponsored an exchange between Harold Netland, Jim Beilby, Doug Geivett, and Dolores Morris around Netland's 2022 book, Religious Experience and the Knowledge of God. I briefly orient readers to the resulting Philosophia Christi symposium by saying a few words introducing Harold Netland and some key themes in his argument that a "critical trust" approach to religious experience offers modest - but significant - epistemic support for Christian belief and practice.